When rebels turn protesters: demobilized insurgents and social uprisings in Colombia - Sponsel, CD (2023)
Following civil conflict peace agreements, societies often continue to experience political volatility. Cleavages that provided reasons for some society segments to seek armed action may still exist, and violence might have increased political polarization. Consequently, peace process societies often face diverse expressions of discontent, including mass protests. This raises the question of if and how demobilized armed group members behave in such protests. Are they willing to participate and use protests as a new form to articulate their interests and political demands? What implications does their participation have for protest dynamics and political stability? How does the rest of society react to such protest participation?